Temporal modulation of the four-peaked longitudinal structure of the equatorial ionosphere by the 2 day planetary wave - Liu, Guiping; Immel, Thomas J.; England, Scott L.; Kumar, Karanam K.; Ramkumar, Geetha (Journal of Geophysical Research: Space Physics, 2010)
Observations of electron densities by the Constellation Observing System for Meteorology, Ionosphere, and Climate in August to October 2008 have shown a prominent four‐peaked longitudinal structure in the height of the F2 layer (hmF2) in the equatorial ionosphere. The development of this ionospheric structure in daytime is found to be consistent with the forcing by the eastward‐propagating nonmigrating diurnal tide with zonal wave number 3 (DE3). It is believed that tidal winds can modify the E region electric fields and subsequently produce variations in the ionosphere through the dynamo effect. This study reveals that the amplitude of the hmF2 four‐peaked longitudinal structure is subject to a 2 day periodic modulation on certain intervals in the two‐month time period. Simultaneously, wind measurements from the SKiYMET meteor radar at Thumba (8.5°N, 77°E), India indicate corresponding 2 day planetary wave activity in the mesosphere and lower thermosphere (MLT). The 2 day planetary wave has both zonal and meridional wind components, and it is the variability in the zonal component that most closely corresponds to F2 layer changes. The zonal wind observations by the radar also show that the amplitude of the diurnal tide is modulated by the 2 day wave. This study suggests that the identified 2 day variation of the hmF2 four‐peaked longitudinal structure in the equatorial ionosphere is caused by the interaction between the DE3 tide and the 2 day planetary wave.